Guiding the Process of Construct Building: An Exploration Based on Heidegger’s Ontological Difference - Gierl, Heribert (Philosophy and Realistic Reflection, 2025)
Numerous academic disciplines are dedicated to the study of human behavior. Within these disciplines, a well-established standard governs the conduct of research, encompassing construct building, theory formulation, measurement development, and statistical analysis. While literature provides extensive criteria to ensure the quality of theory formulation, measurement construction, and the use of statistical procedures, comparatively little attention has been paid to ensuring the quality of construct building. This work begins by seeking to clarify different conceptions of the nature of constructs. We posit that they are assumed to be invented, developed, or disclosed. Our first aim is to discuss the option that constructs are equal to disclosed reality. Drawing on Heidegger’s ontological difference, we propose that this philosophical framework offers a lens through which this option can be understood. Our second aim is to explore how researchers can provide evidence for the existence of a particular construct depending on the construct’s nature. Our third objective is to examine whether Heidegger’s philosophy can inform the derivation of criteria for the quality of construct conceptualization. From this analysis, we propose a separation between the definitional and clarificatory parts of disclosed constructs. Their definitional component should be articulated independently of temporal and spatial contingencies. The disclosure of the clarificatory component should emerge through an iterative ontic-ontological process and allow for such contingencies. Furthermore, we advocate for the reporting of the stage of disclosure reached within the hermeneutic process. To illustrate the practical applicability of these proposed criteria, we examine the marketing construct of brand age.